Salvianolic acid A inhibits angiotensin II-induced proliferation of human umbilical vein endothelial cells by attenuating the production of ROS - Yang, Luan-luan (Nature Publishing Group, 2012)
AIM: To investigate the action of salvianolic acid A (SalA) on angiotensin II (Ang II)-induced proliferation of human umbilical vein endothelial cells (HUVECs) and the possible signaling pathways mediating this action. METHODS: Cell proliferation was examined with MTT assay. The expression levels of Src phosphorylation (phospho-Src), Akt phosphorylation (phospho-Akt), and NADPH oxidase 4 (Nox4) in HUVECs were determined by Western blot. The production of reactive oxygen species (ROS) was estimated using fluorescence-activated cell sorting (FACS). RESULTS: SalA (6.25–50 μmol/L) did not affect the viability of HUVECs. Treatment of HUVECs with Ang II (1 μmol/L) markedly increased the cell viability; pretreatment of HUVECs with SalA (12.5, 25 and 50 μmol/L) prevented Ang II-induced increase of the cell viability in a concentration-dependent manner. Treatment of HUVECs with Ang II (1 μmol/L) markedly up-regulated the protein expression levels of phospho-Src, phospho-Akt (473) and Nox4; pretreatment of HUVECs with SalA (12.5, 25 and 50 μmol/L) blocked all the effects in a concentration-dependent manner. Treatment of HUVECs with Ang II (1 μmol/L) dramatically increased ROS production in HUVECs; pretreatment of HUVECs with SalA (12.5, 25 and 50 μmol/L) blocked the ROS production in a concentration-dependent manner. CONCLUSION: SalA inhibits Ang II-induced proliferation of HUVECs via reducing the expression levels of phospho-Src and phospho-Akt (473), thereby attenuating the production of ROS.